Pyoderma Gangrenosum After Bilateral Total Knee Arthroplasty - Reilly Loomis, PA-C (Elsevier, 2021)
Pyoderma gangrenosum is a neutrophilic dermatosis, which mimics both infection and necrotizing fasciitis, that can present after surgical interventions. We present the case of a 62-year-old male who underwent one-stage bilateral total knee arthroplasty. Nine days after the surgery, he presented with wound breakdown, high fever, and elevated white blood cell count. Repeated debridement was performed, and empiric antibiotics were given. All tissue cultures and aspirates remained negative throughout treatment course, and the patient remained unresponsive to therapy. The patient was eventually diagnosed with pyoderma gangrenosum after infectious etiologies were ruled out and after a skin biopsy and dermatologic consultation. His condition rapidly improved after treatment with corticosteroids, and soft-tissue defects were repaired with skin substitute and full-thickness skin grafting. In patients with aseptic wound breakdown after total knee arthroplasty, pyoderma gangrenosum is a rare but devastating complication and should be considered.